2005
DOI: 10.1124/jpet.105.093195
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cyclooxygenase-2 and Prostacyclin/IP Receptors in Mucosal Defense against Ischemia/Reperfusion Injury in Mouse Stomach

Abstract: We examined the roles of cyclooxygenase (COX) isozymes, prostaglandins (PGs), and their receptors in the mucosal defense against ischemia/reperfusion (I/R)-induced gastric lesions in mice. Male C57BL/6 mice, including wild-type animals and those lacking prostaglandin E 2 (EP)1, EP3, or prostaglandin I 2 (IP) receptors, were used after 18 h of fasting. Under urethane anesthesia, the celiac artery was clamped (ischemia) for 30 min, and then reperfusion was achieved for 60 min through the removal of the clamp, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 43 publications
7
37
0
Order By: Relevance
“…Under the experimental conditions, the increased COX-2 expressed in the endothelial cells played a protective role against gastric injury induced by I/R (17,59). However, COX-1 has demonstrated inconsistent findings with regard to its role in gastric mucosa damaged by I /R with some studies assigning it a protective or neutral role (33,60) and another giving it an aggressive role (59).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Under the experimental conditions, the increased COX-2 expressed in the endothelial cells played a protective role against gastric injury induced by I/R (17,59). However, COX-1 has demonstrated inconsistent findings with regard to its role in gastric mucosa damaged by I /R with some studies assigning it a protective or neutral role (33,60) and another giving it an aggressive role (59).…”
Section: Discussionmentioning
confidence: 94%
“…The nucleotide sequences of the primers were as follows: β-actin: sense, 5' TTG TAA CCA ACT GGG ACG ATA TGG 3' and antisense, 5' GAT CTT GAT CTT CAT GGT GCT AGG 3'; COX-1: sense, 5' CTG CAT GTG GCT GTG GAT GTC ATC 3' and antisense, 5' GGT CTT GGT GAG GCA GAC CAG 3'; COX-2: sense, 5' TGA TGA CTG CCC AAC TCC CAT G 3' and anti-sense, 5' AAT GTT GAA GGT GTC CGG CAG C 3'. The primer sequences for β-actin, COX-1, and COX-2 were based on the sequences of their published cDNA (17,27). The polymerase chain reaction products were detected by electrophoresis on a 1.5% agarose gel in Tris-EDTAacetic acid buffer containing ethidium bromide.…”
Section: Cox Expression By Reverse Transcription Polymerase Chain Reamentioning
confidence: 99%
See 1 more Smart Citation
“…An aliquot of the reverse transcription reaction product served as a template for 35 PCR cycles consisting of 1-min denaturation at 94˚C, 0.5 min annealing at 56˚C, and 1-min extension at 72˚C in a thermal cycler. A portion of the PCR mixture was electrophoresed in a 1.5% agarose gel in Tris-EDTA-acetic acid buffer, and the gel was stained with ethidium bromide and photographed (20).…”
Section: Methodsmentioning
confidence: 99%
“…Some experimental studies have demonstrated that free radicals, lipid peroxidation and neutrophils infiltration in gastric mucosa play important roles in the pathogenesis of acute gastric lesions induced by I/R (Andrews et al, 1994a;Kitahora & Guth, 1987). Moreover, it has been demonstrated that various other factors, such as prostaglandins and nitric oxide (NO), play pathogenic roles in these gastric lesions (Kotani et al, 2006;Naito et al, 1998).…”
Section: Introductionmentioning
confidence: 99%